2012
DOI: 10.1021/jp309726v
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine–Lactose Permease Interaction: A Comparative Study Based on FRET

Abstract: In this work we have investigated the selectivity of lactose permease (LacY) of Escherichia coli (E. coli) for its surrounding phospholipids when reconstituted in binary mixtures of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE), 1,2-Palmitoyl-sn-glycero-3-phosphoethanolamine (DPPE), or 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) with 1-palmitoyl-2-oleoyl-sn-glycero-3-(phospho-rac-(1-glycerol)) (POPG). Förster resonance energy transfer (FRET) measurements have been performed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…According to the data in Figure , these areas were 0.68, 0.80, and 0.90 nm 2 ·molecule –1 for DPPE, POPE, and DOPE, respectively, and 0.59, 0.68, and 0.79 nm 2 ·molecule –1 for DPPE:POPG, POPE:POPG, and DOPE:POPG mixed monolayers. The fitted values of μ show that the lipid selectivity of LacY is DOPE ∼ POPE > DPPE. Besides, the DPPE:POPG mixture for which we have observed a double collapse in the monolayer seems not fulfill the requirements on surface lateral pressure of LacY. However, these data confirm that the molecular area occupied by a phospholipid, and hence the physical state of the phospholipid, are relevant in TMP–lipid interactions.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the data in Figure , these areas were 0.68, 0.80, and 0.90 nm 2 ·molecule –1 for DPPE, POPE, and DOPE, respectively, and 0.59, 0.68, and 0.79 nm 2 ·molecule –1 for DPPE:POPG, POPE:POPG, and DOPE:POPG mixed monolayers. The fitted values of μ show that the lipid selectivity of LacY is DOPE ∼ POPE > DPPE. Besides, the DPPE:POPG mixture for which we have observed a double collapse in the monolayer seems not fulfill the requirements on surface lateral pressure of LacY. However, these data confirm that the molecular area occupied by a phospholipid, and hence the physical state of the phospholipid, are relevant in TMP–lipid interactions.…”
Section: Resultsmentioning
confidence: 74%
“…One of the aims of this work was to provide information on how physical properties of POPE may influence the physiological activity of LacY. As a member of the major facilitator superfamily, LacY is considered a paradigm for secondary transporters transport, the structure and function of which have been well established. , We have demonstrated previously that POPE lipid molecules are in close contact with LacY and the requirement of PEs for the correct folding of LacY in proteoliposomes has also been reported . The mechanism of action of LacY involves several steps between an initial inward-facing (∨ shape facing the periplasm) to an outward-facing (∧ shape facing the cytoplasm) conformation.…”
Section: Resultsmentioning
confidence: 99%
“…These results support the stabilization role of motif A in the charge-dipole interaction. Many mutations at the +5 position of motif A in a number of MFS proteins were found to be detrimental to the transport function (33,34,36,37). For example, an Asp-to-Asn variant of Tn10 completely lost its activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lensink et al concluded that lipid-mediated salt-bridges are important determinants of LacY state stabilization. This mechanism of lipid-specific transporter function modulation was tested in a FRET study by Suárez-Germà et al The D/C mutation of the conserved aspartate identified by MD studies was experimentally proven to considerably change LacY selectivity for lipids. Recently, Martens et al combined hydrogen–deuterium exchange mass spectrometry (HDX-MS) with simulations and showed how the specific interactions between PE lipid headgroups and conserved charged residues (including the aspartate describe above) regulate the conformational equilibrium of the transporter .…”
Section: Slc Transportersmentioning
confidence: 99%